A Cadaveric Study of Ultrasound-Guided Maxillary Nerve Block Via the Pterygopalatine Fossa: A Novel Technique Using the Lateral Pterygoid Plate Approach. Issue 6 (August 2018) - Kampitak, Wirinaree; Tansatit, Tanvaa; Shibata, Yasuyuki
Abstract : Background and Objectives: This study aimed to describe and assess the accuracy and feasibility of a novel technique for ultrasound-guided maxillary nerve block using the lateral pterygoid plate (LPP) approach via the pterygopalatine fossa (PPF) in a soft cadaveric model. Methods: Ten soft cadavers were studied. The curved array ultrasound transducer probe was applied over 1 side of the face of the cadavers in the open-mouth posture. It was placed transversely below the zygomatic arch for identifying the border of the maxillary tuberosity and the LPP. We tilted the curve probe from the caudal to the cranial direction until the uppermost part of the PPF was identified. The in-plane needle approach was used from the anterior-to-posterior and lateral-to-medial directions through the fossa, and 3 mL of methylene blue dye was injected. Results: The spread of injectate after ultrasound-guided maxillary nerve block using the LPP approach was successfully performed in all cadavers as demonstrated by visualized moderate to marked traces of methylene blue within the PPF. No accidental injections in the maxillary arteries or facial nerves were observed. Conclusions: This cadaveric study suggests that ultrasound-guided maxillary nerve block using the LPP approach via the PPF has a high degree of accuracy and feasibility. Further studies are required to confirm its efficacy and safety for clinical application.